Caracterização da atividade genotóxica e citotóxica de meso-tetra-(piridil)-porfirinas contendo complexos de paládio (II) e platina (II) - Trentin, Luana Beló (2024)
Porphyrins are widely used molecules as photosensitizers (PS) since they possess several crucial characteristics for their use in photodynamic therapy (PDT). PDT is a versatile alternative employed in the treatment of various diseases. It uses a light source, oxygen, and a photosensitizer (PS) to induce cell death or inactivate microorganisms through the production of reactive oxygen species (ROS). This study characterized the interaction of meso-tetra-pyridyl-porphyrins containing peripheral complexes of Pd(II) and Pt(II) (3-PdTPyP, 4-PdTPyP, 3-PtTPyP, and 4-PtTPyP) with DNA, evaluating their genotoxic and cytotoxic capabilities. The results indicate that 3-PdTPyP and 4-PdTPyP interact with DNA in a non-interactive manner, preferably in the minor groove, through intramolecular van der Waals forces. 3-PtTPyP proved to be particularly effective in inducing oxidized purines, leading to DNA degradation at higher concentrations (10.5 μM), both under white light and in the dark. These findings were confirmed by plasmid DNA inactivation (RF) analysis in E. coli (strain MBL50), highlighting a pronounced pattern of genotoxicity of this porphyrin. Cell viability assays with human melanoma cell line (A375), murine melanoma (B16-F10), and murine fibroblast (L929) revealed more pronounced cytotoxic effects under white light compared to the dark, highlighting the differential cytotoxicity between porphyrins in melanoma and fibroblast cell lines. 3-PdTPyP demonstrated higher cytotoxicity under light conditions in A375, with a reduction in the percentage of cell viability starting from 64.99%, while 4-PdTPyP showed significant efficacy in B16-F10, resulting in a reduction of 55.20% Notably, 3-PtTPyP exhibited superior cytotoxicity in melanoma cell lines compared to all tested porphyrins. Cellular nitric oxide production analyses revealed that Pd(II) porphyrins did not significantly affect NO production, while 3-PtTPyP showed small modulations depending on the cell line and concentration. Keywords: Pd (II) porphyrins. Pt (II) porphyrins. Photodynamic therapy. Genotoxicity.